A vallási öntudat formálódása az Üdvhadsereg magyarországi alapításának példáján - Hecker-Réz , Róbert (Kultúratudományi Szemle, 2024)
The formation of religious self-awareness on the example of the founding of the Salvation Army in Hungary In this article, I would like to present the phenomenon of religious self-consciousness in the context of identity development. This is of central importance in our current era, characterised by a cultural struggle between different religions, because, according to my intention, it also underpins the need for permanent identity renewal – and, thus, religious self-image. In this article, I describe the dynamics of selfconfidence development within the interpretative framework of religious selfconfidence. I illustrate this as an example using the budding religious self-confidence of the Hungarian Salvation Army. However, the main focus of the article is not historical review. The components illustrated by the rich source material may also be important from the perspective of current challenges regarding religious selfconfidence development. Furthermore, I also hope that the content of this selfconfidence development can inspire all those looking for authentic role models on the way to their own search for identity. In this way, the Hungarian Salvation Army's religious self-awareness prototypes can help develop self-awareness in both the ecumenical and individual spheres.